2014
DOI: 10.1007/s00381-014-2375-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of levetiracetam on hypoxic ischemic brain injury in neonatal rats

Abstract: Based on these results, we believe that one mechanism of levetiracetam's neuroprotective effects is due to increases in glutathione peroxidase and superoxide dismutase enzyme levels. To the best of our knowledge, this study is the first to show the neuroprotective effects of levetiracetam in a neonatal rat model of hypoxic-ischemic brain injury using histopathological, biochemical, and late-period behavioral experiments within the same experimental group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Indeed, ischemia caused accumulation of lactic acid because of anaerobic glycolysis leading to increased membrane permeability and consecutive edema formation. Sanchez et al 28 and Komur et al 29 pointed that LEV contributed favorably to the learning abilities of the rats and rescued memory deficits in hypoxicischemic brain injury and Alzheimer's disease model, respectively. 25 F I G U R E 3 A, Photomicrograph of the cerebral cortex of control group showing evenly distributed variable sized neuronal cells surrounded by eosinophilic neurofibrillary material, which contains normal glial cells: astrocytes and oligodendrocytes (H&E ×400).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ischemia caused accumulation of lactic acid because of anaerobic glycolysis leading to increased membrane permeability and consecutive edema formation. Sanchez et al 28 and Komur et al 29 pointed that LEV contributed favorably to the learning abilities of the rats and rescued memory deficits in hypoxicischemic brain injury and Alzheimer's disease model, respectively. 25 F I G U R E 3 A, Photomicrograph of the cerebral cortex of control group showing evenly distributed variable sized neuronal cells surrounded by eosinophilic neurofibrillary material, which contains normal glial cells: astrocytes and oligodendrocytes (H&E ×400).…”
Section: Discussionmentioning
confidence: 99%
“…Following reports of the neuroprotective effects of LEV and several subsequent experimental studies, many researchers have begun to wonder if LEV could be useful in treating neonatal HIBI (13)(14)(15). Kilicdag et al (13) administered intraperitoneal LEV 80 mg.kg -1 to 7-d-old rats following hypoxia and continued administering LEV 40 mg×kg -1 ×d -1 for 7 d, and reported a signifi cant decrease in neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, higher doses of LEV than previously studied (400 and 800 mg.kg -1 ) were administered in a neonatal rat model of HIBI, based on earlier reports of a dose-dependent neuroprotective effect (14) and because numerous animal studies did not report toxic effects at LEV dose of 1000-1500 mg.kg -1 (12). As reported by Kilicdag et al (13) and Komur et al (14), LEV was observed to be neuroprotective in the present study's neonatal rats with HIBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations